Beyond bars a rehabilitative Binan City Jail - Balboa, Alleli S.; Bulaong, Jesus Apolinario (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
Currently, there is an increasing trend in the population of incarcerated people in the Philippines. A spike in the population in 2016 may be attributed to the current administration's anti-drug campaign. The country now house the most overcrowded correctional facilities in the world at a congestion rate of 540.84%. With no provision of additional facilities for these people, they are forced to be packed in dormitory rooms almost six times smaller than ideal for their number. This then leads to more issues with respect to humanitarian, health, and security of the users, which in turn hinders rehabilitation, which is supposedly the main goal of the facility. Often, architecture is merely associated with the physical planning of spaces. However, this thesis aims to bring light to the practice of architecture as a means of aid in the people deprived of liberty's (PDLs) rehabilitation. With this, it is important to plan and design a city jail that goes beyond bars; beyond the idea of merely isolating PDLs. It is also more than just providing them with the proper cell dimensions. Instead, it employs a normalization principle, both in the physical and social interaction aspect. Normalizing the environment at which the PDLs live in, yields better psychological well-being and will therefore result in a better and more normal behavior, will encourage PDLs' participation, reduce stress, incidents and assaults. This, in turn, benefits the society, as these people, who used to be criminals, will now become productive members of the society.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: City Jail -- Philippines